alpha(1G) T-type calcium channel selectively regulates P-selectin surface expression in pulmonary capillary endothelium - Zhou, Chun; Chen, Hairu; King, Judy A.; Sellak, Hassan; Kuebler, Wolfgang M.; Yin, Jun; Townsley, Mary I.; Shin, Hee-Sup; Wu, Songwei (AMER PHYSIOLOGICAL SOC, 2010)
Zhou C, Chen H, King JA, Sellak H, Kuebler WM, Yin J, Townsley MI, Shin HS, Wu S. alpha(1G) T-type calcium channel selectively regulates P-selectin surface expression in pulmonary capillary endothelium. Am J Physiol Lung Cell Mol Physiol 299: L86-L97, 2010. First published April 30, 2010; doi:10.1152/ajplung.00331.2009.-Regulated P-selectin surface expression provides a rapid measure for endothelial transition to a proinflammatory phenotype. In general, P-selectin surface expression results from Weibel-Palade body (WPb) exocytosis. Yet, it is unclear whether pulmonary capillary endothelium possesses WPbs or regulated P-selectin surface expression and, if so, how inflammatory stimuli initiate exocytosis. We used immunohistochemistry, immunofluorescence labeling, ultrastructural assessment, and an isolated perfused lung model to demonstrate that capillary endothelium lacks WPbs but possesses P-selectin. Thrombin stimulated P-selectin surface expression in both extra-alveolar vessel and alveolar capillary endothelium. Only in capillaries was the throm-bin- stimulated P-selectin surface expression considerably mitigated by pharmacologic blockade of the T-type channel or genetic knockout of the T-type channel alpha(1G)-subunit. Depolarization of endothelial plasma membrane via high K+ perfusion capable of eliciting cytosolic Ca2(+) transients also provoked P-selectin surface expression in alveolar capillaries that was abolished by T-type channel blockade or alpha(1G) knockout. Our findings reveal an intracellular WPb-independent P-selectin pool in pulmonary capillary endothelium, where the regulated P-selectin surface expression is triggered by Ca2(+) transients evoked through activation of the alpha(1G) T-type channel.
Keywords: VON-WILLEBRAND-FACTOR; ACUTE LUNG INJURY; GRANULE MEMBRANE-PROTEIN; WEIBEL-PALADE BODIES; IN-VIVO; CELL-ADHESION; LEUKOCYTE SEQUESTRATION; VONWILLEBRAND-FACTOR; TISSUE DISTRIBUTION; CA2+ CHANNELS